CGIAR gender equality initiative - Awinoh, Martha (CGIAR Initiative on Gender Equality, 2023)
The first edition of HER Voice, the official newsletter of the CGIAR gender equality research initiative (HER+) highlights the significant strides made by HER+. Our achievements include the development of a gendered social norms index, a pioneering framework for women-led climate-smart socio-technical innovation bundles, a comprehensive review of gendered resilience through social protection design, and the unveiling of the Women’s Empowerment in Agrifood System Governance Assessment Tool (WEAGov). This newsletter features a video story where Regina Serem, a farmer from the Boitok Farm community in Kenya, shares her experiences with women-led socio-technical innovation bundles. Additionally, it offers updates from HER+ TRANSFORM, EMPOWER, PROTECT, and VOICE work packages, complete with links to our latest publications.